Agriculture in urban planning : (Earthscan Publications Ltd., 2009)
This volume, by the world’s leading experts on urban agriculture, examines concrete strategies to integrate city farming into the urban landscape. Drawing on original field work in cities across the rapidly urbanizing global south, the book examines the contribution of urban agriculture and city farming to livelihoods and food security. Case studies cover food production; diversification for robust and secure food provision; the socio-economic and agronomic aspects of urban composting; urban agriculture as a viable livelihood strategy; strategies for integrating city farming into urban landscapes; and the complex social-ecological networks of urban agriculture. Other case studies look at public health aspects including the impact of pesticides, microbiological risks, pollution and water contamination on food production and people. Ultimately the book calls on city farmers, politicians, environmentalists and regulatory bodies to work together to improve the long term sustainability of urban farming as a major, secure source of food and employment for urban populations.